SEPARATION MECHANISM AND TECTONOSTRATIGRAPHY OF SOUTH MAKASSAR BASIN, SOUTH SULAWESI - Syauqi Hidayatillah, Ahmad
South Makassar Basin (SMB) is an offshore basin located at southern part area between Kalimantan Island and Sulawesi Island. This basin has been explored for a long time, but until now does not resulting any satisfying discovery. The research conducted to know separation mechanism at SMB whether by strike-slip or by rifting, and to know its tectonostratigraphy. To answer the objectives of the research, primary data consisted of seismic and well data, also secondary data consisted of bathymetry map, elevation model map, and bouger anomaly map has been used. The methods used in this research are: analyzing time structure section, making of time structure map, making isochron map, analyzing depositional environment, analyzing trend of the faults, and also palinspastic reconstruction. Interpretation of time structure sections showed that developed structures in SMB are normal faults, thrust faults, inversion faults, and folds. Time structure map of basement showed there are two trends of fault alignments developed: NW – SE trend and NE – SW trend. The form of normal faults, the trend of basement faults that dominated by NE – SW, also with alignment trend on bouger anomali map indicating that separation mechanism of SMB is rifting related with principal direction of separation NW – SE. The asymetric geometry of normal faults also with palinspastic reconstructions showed that SMB has simple shear separation model. Interpretation of seismic reflectors and strain analysis from palinspastic reconstructions showed there are three tectonic phases in SMB: rifting phase, sagging phase, and inversion phase. Tectonostratigraphy of SMB can be divided into four units: Pre-rift Unit, Syn-rift Unit, Post-rift Unit, and Syn-inversion Unit.